Teletandem and literature: intercultural experiences in teaching Portuguese as a foreign language teaching - Ramos, Karin Adriane Henschel Pobbe [UNESP]; da Silva, Mayara Nunes [UNESP] (My University, 2022)
Teletandem is characterized as a telecollaborative context for language learning and has been developed as an enabling environment for the dissemination of language, literature and culture (Telles, 2015a; Zakir, 2015; Ramos & Carvalho, 2020). By promoting the interaction between Brazilian students and students from foreign universities, teletandem gives opportunity to participants to learn other language and contributes to dissemination of the teaching of Portuguese as a foreign language (Ramos, 2016). From that contact, tandem participants can also develop an intercultural perspective that encompasses the ways of being and acting socially in the language (Mendes, 2011; Kramsch, 2017). Thus, grounded on an intercultural approach with a discursive basis, we understand culture as historical processes, built on the interaction between subjects who can no longer identify themselves necessarily by their nationally, but by their gender, race, ethnicity, age, affecting, consequently, their ways of using language and meaning (Kramsch & Hua, 2016). Therefore, this paper aims to present some reflections, resulting from our research for a master degree, about the contributions of discussing literary texts to the development of an intercultural teaching of the Portuguese language that leads to an understanding of the symbolic dimension of intercultural exchanges, as well as to a broader and more diverse understanding of culture. For this, we initially present Teletandem Project and its importance for dissemination of teaching Portuguese as a foreign language. And then we explain the intercultural approach with a discursive basis in relation to foreign language teaching in order to demonstrate the relevance of literature for in this learning process. Preliminary results indicate that inserting literary texts in teletandem sessions enables a deepening of discussions and the emergence of more diverse themes and directly related to the realities of the participants.
Teletandem e literatura: experiências interculturais no ensino de português como língua estrangeira
Keywords: interculturality; literature and teaching; portuguese teaching; telecollaboration; teletandem